2021
DOI: 10.52403/ijshr.20211019
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Buteyko Breathing Technique versus Nadi Shuddhi Pranayama to Improve Pulmonary Function in Subjects with Bronchial Asthma

Abstract: Background: Asthma is a chronic life-threatening disease as the airways in the lungs often swollen or inflamed, which makes the airways very sensitive. So, the exposure to the environment in day-to-day life triggers asthma. Asthma can affect at any age group. This study mainly focuses on comparing the effects of Buteyko breathing technique and Pranayama on improving Pulmonary Function in subjects with Bronchial Asthma. Method: Total of 79subjects selected, out of those 66 subjects were included after obtaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The study looked at lung function tests and chest movement. Results showed that diaphragmatic stretching was better than rib stretching for improving both lung function and chest movement in people with COPD [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study looked at lung function tests and chest movement. Results showed that diaphragmatic stretching was better than rib stretching for improving both lung function and chest movement in people with COPD [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
“…Stretching muscle fibers encourages the growth of sarcomeres, which in turn lengthens shortened muscles. A sufficient length of the respiratory muscles would encourage an overall improvement in their ability to contract, as well as a rise in thoracic expansion and benefits to respiratory mechanics performance [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%